Effects of rough handling on short chain fatty acid production and gastrointestinal pH in broilers and modulatory role of Lactobacilli - Meimandipour, Amir; Farjam, Abdoreza Soleimani; Houshmand, Mohammad; Kasim, Azhar; Bejo, Mohd Hair; Mustafa, Shuhaimi; Abd Manap, Mohd Yazid (Academic Journals, 2011)
The influence of stress due to rough handling (RH) on gastrointestinal tract (GIT) environmental pH, concentration of short chain fatty acids (SCFAs) and modulatory roles of two Lactobacillus strains was investigated in broiler chickens. Equal number of chicks was randomly assigned to one of the following treatment groups; (i): no handling + basal diet (control), (ii): RH and + basal diet (RH-BD), (iii): RH + basal diet supplemented with 107 CFU of each Lactobacillus strain per gram of feed (RH-BDL). Birds fed dietary Lactobacilli from day one until the end of the experiment and subjected to RH from day 1 to 21. Digesta from different GIT regions were collected at 14, 28, 35 and 42 days of age and SCFAs and pH were measured. Duodenal, ileal and cecal lactate concentrations together with cecal butyrate level were significantly (P < 0.05) decreased in RH-BD birds compared with the control and RH-BDL at 14 and 21 days of age. Acetate concentration was significantly (P < 0.05) reduced in the jejunum, ileum and cecum of both RH-BD and RH-BDL birds at 14 days of age. It can be concluded that, stressful condition over the course of the GIT microbial development, negatively affected microbial activity by reduction of the lactate, acetate (as the main substrate for butyric producing bacteria) and ultimately butyrate concentration along the GIT and particularly cecum. This adverse effect was effectively ameliorated by Lactobacillus supplementation.